Dynamics of stand density and self-thinning in Chinese fir plantations: theoretical insights and empirical validation - Long, Shisheng; Zeng, Siqi; Wang, Guangxing (Frontiers in Plant Science, 2024)
Stand density management is important for decision-making of adaptive silviculture and thinning, growth modeling and yield prediction of forests especially plantations. Although substantial research related to self-thinning rule and maximum size-density law has been conducted, there are still critical gaps that exist in biophysical explanation and validation of the relationships among stand variables and relevant parameters. In this study, we theoretically explored and validated the relationship between maximum size-density and average diameter at breast height (D) as well as tree height (H). The validation was based on time-series data collected from a 30-year clear-cut, fully stocked Chinese fir plantation, one of China's most important and fast-growing commercial tree species. The growth balance status of the fully stocked stand was proposed, in which before self-thinning happening, the growth rate of the stand basal area (G) was similar to that of the average H, that is, G'⁄((G-b_0 )=H'⁄H) and approaching to a constant, b1, the slope of the relationship G_1.0=b_0+b_1 H. This finding provides a potential measure for selection of fully stocked stands. Generalized maximum size-density and stand density index (SDI) equations were then proposed: N_1.0=A×D^(-2) and SDI=A⋅D^(-2) with A=4×(b_0+b_1 H)/π, in which both N_1.0 and SDI are a function of average D and H, and are different from those of Reineke. In addition, this study also resulted in a generalized self-thinning equation: v=kH^q N_1.0^(-1) or w=c_1 H^q N_1.0^(-1), where k and q are the parameters, c_0 is the biomass density and c_1=c_0×k. This implies that in a fully stocked stand, the tree volume (v) or biomass (w) varies depending not only on the number of trees but also on tree height. The self-thinning rule proposed by Yoda (1963) was not supported by this study. Thus, the findings may help to enhance understanding maximum size-density law and self-thinning boundary rule and provide useful tools for stand density management of Chinese fir plantations.